(untitled) (Research, Society and Development, 2020)
Analyze among the public institutions in Brazil, the disciplines focused on the care of patients with special needs in dentistry courses. This is a observational, documentary cross-sectional study od quantitative approach, where the adopted methodology was described by Penha and Bonato.An form was produced and information about the existence of the discipline, nomenclature, number of hours, disciplinary integration, optional or compulsory discipline and whether the discipline was theoretical or practical were collected on the official websites of the courses. In the North and Midwest, 100% of public institutions offer the discipline of special patients. In the Northeast, Southeast and South only 55%, 71% and 50%, respectively, provide this education. When present, some disciplines about special needs patients are offered in the last periods of the undergraduate course, the majority (32%) in the 9th period. Regarding the other characteristics analyzed (nomenclature, number of hours, period offered, optional or compulsory character, theoretical or practical) it was possible to notice a variation by institution. It appears that some institutions do not have the discipline in their curriculum, however, its inclusion is very important for the formation of a professional who acts on a new logic, focused on humanization and comprehensive care.